2002
DOI: 10.1159/000047759
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty and Stenting for Total Symptomatic Atherosclerotic Occlusion of the Subclavian or Innominate Arteries

Abstract: Bypass grafting is considered the treatment of choice for occlusions of supraaortic vessels. Percutaneous transluminal angioplasty (PTA) is a well-established treatment for patients with subclavian stenosis, but its efficacy in total subclavian or innominate occlusions is so far not well established. Since 1995, we have carried out 9 PTA revascularizations in 9 patients with total symptomatic atherosclerotic occlusion of supraaortic vessels. The technical success rate was 100%, without any major (death or stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…[10][11][12][13] However, endovascular treatment is a high-risk procedure for complicated lesions involving the subclavian arterial orifice, severe stenosis, or totally occluded lesions or cases with ipsilateral VA involvement. 14,15 In this study, we used endovascular treatment to treat 11 complicated cases of severe stenosis or occlusion in the SA, and achieved good clinical outcomes and angiographic patency rates based on a mid-term clinical and angiographic follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] However, endovascular treatment is a high-risk procedure for complicated lesions involving the subclavian arterial orifice, severe stenosis, or totally occluded lesions or cases with ipsilateral VA involvement. 14,15 In this study, we used endovascular treatment to treat 11 complicated cases of severe stenosis or occlusion in the SA, and achieved good clinical outcomes and angiographic patency rates based on a mid-term clinical and angiographic follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, as embolisms occurred in up to 4.3% of patients, it suggests that embolic protection systems may be required while performing SCA interventions 1,2,18 . Considering the anatomic difference between the carotid and vertebral arteries, the use of protective devices can be limited throughout the recanalization procedure 18 . Therefore, we introduced a technique in which a protective device can be safely used throughout the stenting procedure, as described in Figure 2.…”
Section: A B D Cmentioning
confidence: 99%
“…Considering the advancing endovascular stenting techniques and the hereby emerging therapeutic possibilities for targeting stenosis of the intrathoracic segments of supraaortic arteries, 5,6 the importance of more differentiated diagnostic procedures is evident. The significance, which can be attributed to these proximal stenoses concerning the risk of arterio‐embolic cerebral ischemia, is yet unclear.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 A more recent whole body magnetic resonance angiography (MRA) based study revealed 13 stenoses of the subclavian artery (SA) and/or the IA among 32 high-risk patients with known peripheral artery occlusive disease. 4 Considering the advancing endovascular stenting techniques and the hereby emerging therapeutic possibilities for targeting stenosis of the intrathoracic segments of supraaortic arteries, 5,6 the importance of more differentiated diagnostic procedures is evident. The significance, which can be attributed to these proximal stenoses concerning the risk of arterio-embolic cerebral ischemia, is yet unclear.…”
Section: Introductionmentioning
confidence: 99%